2019
DOI: 10.1049/el.2018.7297
|View full text |Cite
|
Sign up to set email alerts
|

5 GHz laterally‐excited bulk‐wave resonators (XBARs) based on thin platelets of lithium niobate

Abstract: In a free-standing 400-nm-thick platelet of crystalline ZY-LiNbO 3 , narrow electrodes (500 nm) placed periodically with a pitch of a few microns can eXcite standing shear-wave bulk acoustic resonances (XBARs), by utilising lateral electric fields oriented parallel to the crystalline Y-axis and parallel to the plane of the platelet. The resonance frequency of ∼4800 MHz is determined mainly by the platelet thickness and only weakly depends on the electrode width and the pitch. Simulations show quality-factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(54 citation statements)
references
References 8 publications
1
53
0
Order By: Relevance
“…Similarly, the degradation from the perceived k 2 is due to the existence of the in-band spurious modes (Modes 2-9 in Table V). Compared to prior A1 mode resonators in conventional Z-cut LiNbO 3 above 3 GHz [38]- [40], the S2 mode resonator in the COP platform shows an improved Q (above 600) with a similar k 2 (above 20%). The S6 resonance at 9.045 GHz shows a perceived k 2 of 3.80% and a 3-dB Q of 660 [ Fig.…”
Section: A Complementarily Oriented Bi-layer Acoustic Resonatormentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, the degradation from the perceived k 2 is due to the existence of the in-band spurious modes (Modes 2-9 in Table V). Compared to prior A1 mode resonators in conventional Z-cut LiNbO 3 above 3 GHz [38]- [40], the S2 mode resonator in the COP platform shows an improved Q (above 600) with a similar k 2 (above 20%). The S6 resonance at 9.045 GHz shows a perceived k 2 of 3.80% and a 3-dB Q of 660 [ Fig.…”
Section: A Complementarily Oriented Bi-layer Acoustic Resonatormentioning
confidence: 88%
“…For more information, see https://creativecommons.org/licenses/by/4.0/ LiNbO 3 for operation beyond 3 GHz. The thinner film leads to more severe surface losses [16], thus limiting the quality factor (Q) of the demonstrated A1 resonators (below 400 [38]- [40]), and the propagation loss (PL) of A1 ADLs (above 0.02 dB/μm [47]). Moreover, lateral field excited A1 devices with spurious mode suppression have a small capacitance per unit area [48].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, acoustic devices using the first-order antisymmetric (A1) mode in Z-cut LiNbO3 have been reported with high k 2 and low loss above 4 GHz [57]- [59]. Different from SH0 and S0, A1 is higher-order in the thickness direction, thus significantly enhancing vp in in-plane dimensions [60] and improving frequency scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sc-LN LVRs utilizing the first-order asymmetric modes (A 1 ) have gained considerable attention due to its high acoustic velocity (>10,000 m/s) and large electromechanical coupling (>10%) [ 125 , 126 ]. It has been demonstrated that sc-LN LVRs operating in A 1 mode can achieve resonant frequency as high as 5 GHz with k eff 2 of 25% [ 127 , 128 ]. However, the reported Qs of sc-LN LVRs remain comparatively low relative to AlN LVRs.…”
Section: Discussionmentioning
confidence: 99%